Inflammation Biomarkers of Advanced Disease in Nongingival Tissues of Chronic Periodontitis Patients - Thiago Alvares da Costa; Marcelo José Barbosa Silva; Polyanna Miranda Alves; Javier Emílio Lazo Chica; Emilio Zorzo Barcelos; Max Antonio Alves Giani; Gustavo Pompermaier Garlet; João Santana da Silva; Virmondes Rodrigues Júnior; Denise Bertulucci Rocha Rodrigues; Cristina Ribeiro de Barros Cardoso (Hindawi Limited, 2015)
Chronic periodontitis is a multifactorial inflammatory disease that affects supporting structures of the teeth. Although the gingival response is largely described, little is known about the immune changes in the alveolar bone and neighboring tissues that could indicate periodontal disease (PD) activity. Then, in this study we identified the ongoing inflammatory changes and novel biomarkers for periodontitis in the tissues directly affected by the destructive disease in PD patients. Samples were collected by osteotomy in 17 control subjects during extraction of third molars and 18 patients with advanced PD, in which alveoloplasty was necessary after extraction of teeth with previous extensive periodontal damage. Patients presented mononuclear cells infiltration in the connective tissue next to the bone and higher fibrosis area, along with increased accumulation of IL-17+ and TRAP+ cells. The levels of TNF-α and MMP-2 mRNA were also elevated compared to controls and a positive and significant correlation was observed between TNF-α and MMP-2 mRNA expression, considering all samples evaluated. In conclusion, nongingival tissues neighboring large periodontal pockets present inflammatory markers that could predict ongoing bone resorption and disease spreading. Therefore, we suggested that the detailed evaluation of these regions could be of great importance to the assessment of disease progression.